MEDIASI ADVERSITY QUOTIENT PADA PENGARUH SELF CONFIDENCE TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS DI SMK MAARIF NU BAWANG - Rahmasari, Putri Awaliah; Utami, Rini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematical critical thinking ability is one of the abilities that students must have in learning mathematics. However, in reality, this ability is still in the low category which is influenced by various internal factors, including self confidence and adversity quotient. This study aims to dtermine the effect of self confidence on mathematical critical thinking ability through adversity quotient as a mediating variable. This study applies a quantitative methode through an ex-post facto design. All grade X students of SMK Ma’arif NU Bawang were designated as the population, of which 60 students were taken asa samples using the cluster random sampling method. Data collection utilized a mathematical critical thinking ability test on statistics material as well as a self-confidence and adversity quotient questionnaire. Path analysis technique was chosen as the data analysis method with the help of R software and the Sobel test. Self-confidence was proven to have a significant positive influence on mathematical critical thinking ability with a percentage of 25.21%. In addition, the adversity quotient was able to mediate the influence of self-confidence on mathematical critical thinking ability with a percentage of 6.87%. Based on the Sobel test results, a p-value of <0.05 was obtained, indicating a significant mediation effect. This indicates that the adversity quotient functions as a partial mediator, bridging the relationship between self-confidence and mathematical critical thinking skills.